Until Debt Do Us Part : Subnational Debt, Insolvency, and Markets - Canuto, Otaviano; Liu, Lili (Washington, DC: World Bank, 2013)
With decentralization and urbanization, the debts of state and local governments and of quasi-public agencies have grown in importance. Rapid urbanization in developing countries requires large-scale infrastructure financing to help absorb influxes of rural populations. Borrowing enables state and local governments to capture the benefits of major capital investments immediately and to finance infrastructure more equitably across multiple generations of service users.